Warm Season (Summer) Forage Legume Guide - Yoana C. Newman; C. G. Chambliss (EDIS, 2007)
Revised! SS-AGR-48, a 5-page guide by Y.C. Newman and C. G. Chambliss, provides an overview of summer forage legume crops: inoculation of seeds, cultivars, planting, fertilization, irrigation, and management and utilization for both pasture and hay. Includes a table of planting dates, seeding rates, and planting depths for various forage legume crops. Published by the UF Department of Agronomy, May 2007.